An immunological electrospun scaffold for tumor cell killing and healthy tissue regeneration. Issue 6 (24th August 2018) - Liu, Xingzhi; Zhang, Hongbo; Cheng, Ruoyu; Gu, Yanzheng; Yin, Yin; Sun, Zhiyong; Pan, Guoqing; Deng, Zhongbin; Yang, Huilin; Deng, Lianfu; Cui, Wenguo; Santos, Hélder A.; et al.
Abstract : An immunological tissue engineering scaffold is fabricated using anti-CD40 antibody grafted in electrospun fibers for inducing cancer cell apoptosis, activating immune response and promoting healthy tissue regeneration. Abstract : Antibody-based cancer immune therapy has attracted lots of research interest in recent years; however, it is greatly limited by the easy distribution and burst release of antibodies. In addition, after the clearance of the tissue, healthy tissue regeneration is another challenge for cancer treatment. Herein, we have developed a specific immunological tissue engineering scaffold using the agonistic mouse anti-human CD40 antibody (CD40mAb) incorporated into poly(l -lactide) (PLLA) electrospun fibers through the dopamine (PDA) motif (PLLA-PDA-CD40mAb). CD40mAb is successfully incorporated onto the surface of the electrospun fibrous scaffold, which is proved by immunofluorescence staining, and the PLLA-PDA-CD40mAb scaffold has an anti-tumor effect by locally releasing CD40mAb. Therefore, this immunological electrospun scaffold has very good potential to be developed as a powerful tool for localized tumor treatment, and this is the first to be reported in this area.